The Framework for Android Apps Testing using Mutation Technique - Arshad Javed, Muhammad; Ibrahim, Rosziati; Abdul Wahab, Jahari (IOP conference series. Materials Science and Engineering, 2020)
This paper presents the framework for Android apps testing using mutation technique. A systematic comparative analysis is done based on various approaches and techniques formutation testing. The analysis examines the development of research on this subject and its inspiring objectives and practices. Using comparative analysis, the framework exhibits that Android mutation testing can create assessment cases that are very efficient at distinguishing both naturally happening errors and crowd-sourced errors for Android apps. The framework can be used as a basis to test the Android apps using mutation technique.